2009
DOI: 10.1001/archoto.2009.78
|View full text |Cite
|
Sign up to set email alerts
|

Use of Combination Proteomic Analysis to Demonstrate Molecular Similarity of Head and Neck Squamous Cell Carcinoma Arising From Different Subsites

Abstract: BACKGROUND Squamous cell carcinomas arising from various subsites within the head and neck (HNSCC), while histologically identical, have substantial differences in survival and recurrence rates. Controversy exists as to whether this reflects physical differences between subsites or fundamental molecular heterogeneity. In this study, we used two proteomic approaches to evaluate HNSCCs for differences in protein expression between oral cavity, oropharynx, larynx and hypopharynx subsites. METHODS A tissue micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…Thus, we suggest that the higher expression of p53 plays a role in oral lesion evolution. Other studies have shown conflicting results concerning the p53 and Rb expression in malignant lesions (22). However, Brunotto et al reported that p53 status changes between leukoplakia, oral lichen planus and oral cancer (23).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we suggest that the higher expression of p53 plays a role in oral lesion evolution. Other studies have shown conflicting results concerning the p53 and Rb expression in malignant lesions (22). However, Brunotto et al reported that p53 status changes between leukoplakia, oral lichen planus and oral cancer (23).…”
Section: Discussionmentioning
confidence: 99%
“…Cell lines for paraffin embedding and tissue microarray (TMA) construction methods were as previously described [ 35 ], with antigen retrieval performed using Diva Decloaker (Biocare Medical, Concord, CA, USA) for 1 minute in a 100 °C pressure cooker. Primary antibody incubation was at 4 °C overnight: KRT8 (mouse monoclonal, clone 4.1.18; Millipore, Billerica, MA, USA, 1:150 dilution); cleaved caspase-3 (cCas3, mouse monoclonal, Abcam, Cambridge, MA, USA, 1:150 dilution).…”
Section: Methodsmentioning
confidence: 99%
“…However, another study reported no difference in the expression of molecular markers like p14, p53, cyclin D1, and Rb in the SCCs arising from various sites like the larynx, oropharynx, hypopharynx, and oral cavity. It has been proposed that other factors like viral or chemical agents might be responsible for the observed clinical heterogeneity in these subtypes of SCCs (Weinberger et al , ).…”
Section: Lcm For Integrated Oral Biosciencesmentioning
confidence: 99%